Kinerja Pencapaian Target Kredit sebagai Pemoderasi Hubungan Determinan Perkembangan UMKM: Studi Kasus Pada Bank BRI di Kota Jambi - Shelomita, Cindy; Yuliusman, Yuliusman; Hernando, Riski (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to examine the effect of People's Business Credit (KUR), the use of the BRISpot application, and debtor data accuracy on the development of MSMEs, as well as to determine the role of credit target achievement performance as a moderating variable at Bank BRI in Jambi City. This study employs a quantitative method with a survey approach targeting 100 MSME respondents who received KUR, and the data is analyzed using Structural Equation Modeling (SEM) via the SmartPLS software version 4.0. The results indicate that the accuracy of debtor data from the BRISpot application has a positive and significant effect on MSME development. Meanwhile, KUR and the use of the BRISpot application did not have a significant effect, and Credit Target Achievement Performance was unable to moderate the relationship between the three independent variables and SME development. This indicates that Bank BRI can review its performance appraisal system to focus more on the quality of financing and the sustainability of MSME businesses, rather than solely on the quantity of credit distribution.